PERAN ORANG TUA DALAM PENINGKATAN KUALITAS BELAJAR SISWA BUDDHIS SEKOLAH MENENGAH PERTAMA - Martono, Martono; Waluyo, Waluyo; Kustiani, Kustiani (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2020)
This study aims to describe the role of parents in improving the quality of learning of Buddhist Junior High School students at the District of Getasan. This research uses a qualitative phenomenological method. The subject of this research is the role of parents. The object under this study is the improvement of the quality of learning of Buddhist students. The techniques and the data collection instruments used are interviews, observations, and documentation. The data obtained was tested for its validity using continuous observation, triangulation, and member check. The data analysis was based on the Miles & Huberman model which consisted of data collection, data reduction, data presentation, and concluding, as well as verification. The results of this study include three aspects, namely (1) the form of parental roles, namely attention, caring, and motivating; (2) the impact of parents' attention becomes the spirit of learning, especially learning motivation, enthusiasm in achieving goals, and increasing self-confidence; (3) the meaning of attention from parents for children, that is, gratefulness and become better.